PENURUNAN TINGKAT STRES KERJA PADA PENERBANG MILITER MELALUI PENERAPAN TERAPI YOGA TAWA - Prasetyo, Anggun Resdasari; Nurtjahjanti, Harlina; Fauziah, Nailul; Kustanti, Erin Ratna (Faculty of Psychology, Diponegoro University, 2016)
The laughter yoga therapy is a physical exercise technique that combines yoga breathing techniques, fitness exercise, laughter, applause rhythmic movements, and meditation. The purpose of this study was to test the effect of laughter yoga therapy to reduce work stress levels on military pilots of Indonesian army in Semarang, Central Java. A quasi-experimental pretest-posttest control group design was applied. Subjects comprised 10 military pilots of Indonesian army in Semarang which were compared to 10 military pilots that served ascontrols. Data were collected using the Work Stress Scale (26 items; Î±= .902). The t-test results showed a significant reduced work-stress level after the laughter yoga therapy was applied (t(16.025)=-8.471; p=.00; p<.001).